Two dimensional numerical simulation for compressible flow in thermo-chemical equilibrium - Saldía, Juan P.; Elaskar, Sergio A.; Tamagno, Jose P. (2022)
Fil: Saldía, Juan P. Universidad Nacional de Córdoba. Departamento de Aeronáutica; Argentina.